The Effects of Selective Survival on Black Adults' Cognitive Development. (6th January 2021) - Tan, Shyuan Ching; Gamaldo, Alyssa A; Brick, Timothy; Thorpe, Roland J; Allaire, Jason C; Whitfield, Keith E
Abstract: Objectives: The theory of selective survival suggests that possibly around 70–75 years of age, Blacks may display substantive changes in their pattern of cognitive decline. This study examined the age-graded pattern of cognitive decline within older Blacks by describing a trend that characterizes differences in the change of cognitive decline from ages 51.5 to 95.5, and hypothesized that this age-graded pattern is nonlinear. Method: Utilizing 2 waves of longitudinal data from the Baltimore Study of Black Aging, this study used multilevel modeling to test whether the interaction between age and the 3-year study period (time between waves) had a positive effect on changes in inductive reasoning, declarative memory, working memory, and perceptual speed. Results: A significant positive interaction between age and wave was found for inductive reasoning, demonstrating an age-grade pattern of change/decline in cognitive pattern for Blacks aged 51.5–95.4. Simple slope probing via the Johnson–Neyman Technique suggested that Black adults ~64 years and younger experienced significant decline in inductive reasoning across study time, whereas for those older than 63.71, the decline was nonsignificant. No significant age–wave interactions were found for declarative memory, working memory, or perceptual speed. Discussion: Findings suggest a selective survival effect for inductive reasoning ability among Blacks. With decline evident so early, common cognitive intervention programs targeting adults 65+ may come too late for Blacks, signifying the importance and urgency for early health interventions and public policy designed to promote cognitive reserve.